Insulin requirement profiles of short-term intensive insulin therapy in patients with newly diagnosed type 2 diabetes and its association with long-term glycemic remission. Issue 2 (May 2015) - Liu, Liehua; Ke, Weijian; Wan, Xuesi; Zhang, Pengyuan; Cao, Xiaopei; Deng, Wanping; Li, Yanbing
Highlights: There is a decline of daily insulin dose after euglycemia achieved. The decrement of daily insulin dose is related to reduction of insulin resistance during the therapy. Patients with lowest decline of insulin dose had higher risk of hyperglycemic relapse. Abstract: Aims: To investigate the insulin requirement profiles during short-term intensive continuous subcutaneous insulin infusion (CSII) in patients with newly diagnosed type 2 diabetes and its relationship with long-term glycemic remission. Methods: CSII was applied in 104 patients with newly diagnosed type 2 diabetes. Daily insulin doses were titrated and recorded to achieve and maintain euglycemia for 2 weeks. Measurements of blood glucose, lipid profiles as well as intravenous glucose tolerance tests were performed before and after the therapy. Afterwards, patients were followed up for 1 year. Results: Total daily insulin dose (TDD) was 56.6 ± 16.1 IU at the first day when euglycemia was achieved (TDD-1). Thereafter, TDD progressively decreased at a rate of 1.4 ± 1.0 IU/day to 36.2 ± 16.5 IU at the end of the therapy. TDD-1 could be estimated with body weight, FPG, triglyceride and waist circumference in a multiple linear regression model. Decrement of TDD after euglycemia was achieved (ΔTDD) was associated with reduction of HOMA-IR ( r  = 0.27, P  = 0.008) but not with improvement in β cell function. Patients in the lower tertile of ΔTDD had a significantly higher risk of hyperglycemia relapse than those in the upper tertile within 1 year (HR 3.4, 95%CI [1.4, 8.4], P  = 0.008). Conclusions: There is a steady decline of TDD after euglycemia is achieved in patients with newly diagnosed type 2 diabetes treated with CSII, and ΔTDD is associated with a better long-term glycemic outcome.